Life orientation and social support as determinants of families’ need for home hospice care - Kurowska, Krystyna; Kołodziejska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2008)
The aim of the study was to examine the levels of the sense of coherence (SOC) and support received by the families of home hospice patients, as determinants of need for care and factors preparing family members for the death of loved ones. The study was conducted in the residence places of patients of the Home Care Team of Sue Ryder House, Bydgoszcz. The study included 81 members of families of cancer patients. The SOC level was assessed using the Antonovsky SOC-29 questionnaire and social support was measured using the Kmiecik-Baran scale. The study shows that the patients’ caregivers have different SOC and emotional support levels. Examining these variables helps estimate the scope of care and adjust the kinds of support to the caregivers’ needs, which might influence the quality of care provided by the family at home.